STRATEGI EFEKTIF DALAM MENINGKATKAN MUTU SEKOLAH DI SEKOLAH MERDEKA YOGYAKARTA - Himmah, Aliyatul; Lany Farikha; Subiyantoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In an increasingly competitive world of education, educational institutions must maintain quality to remain relevant and attractive to the community, such as improving the quality of teachers, facilities, and curriculum. An example of innovation in improving the quality of education is Sekolah Merdeka Yogyakarta, which adopts a holistic approach to education, focusing on students' mental and emotional well-being in addition to academic achievement. This research uses a descriptive-qualitative approach and data collected through observation, interviews, and documentation, covering various aspects related to quality improvement strategies implemented by school principals. Data analysis uses data reduction techniques to filter relevant information. The results showed that Sekolah Merdeka Yogyakarta implements a quality management strategy that focuses on students' mental and emotional development, in addition to academic achievement. The strategy includes developing a positive mindset, increasing students' emotional engagement, continuous training for teachers, and holistic assessment that evaluates students' progress as a whole. In addition, the role of parents in supporting children's mental health is an integral part of this strategy. This study shows that the holistic approach implemented by the school creates a balanced educational environment that supports students' academic, social, and emotional development.